2016
DOI: 10.1016/j.ejvs.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Training to Perform Ankle-Brachial Index: Systematic Review and Perspectives to Improve Teaching and Learning

Abstract: According to this systematic review, only few studies, with a low quality rating, have addressed which training program should be performed to provide the best way of teaching how to perform ABI. Future high quality researches are required to define objectively the best training program to facilitate ABI teaching and learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 25 publications
1
43
0
3
Order By: Relevance
“…Several studies have also shown that ABI is not accurately performed in general practice [9 -11]. A possible explanation may be a lack of knowledge about the ABI procedure caused by poor educational processes [12]. Only a few studies [13,14] have addressed the basic knowledge of the ABI procedure among residents and/or students, whereas these results may provide recommendations for optimal medical educational processes.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have also shown that ABI is not accurately performed in general practice [9 -11]. A possible explanation may be a lack of knowledge about the ABI procedure caused by poor educational processes [12]. Only a few studies [13,14] have addressed the basic knowledge of the ABI procedure among residents and/or students, whereas these results may provide recommendations for optimal medical educational processes.…”
Section: Introductionmentioning
confidence: 81%
“…The opportunity to have practical training should be off ered, since the majority of residents (78 %) stated that they would like to receive more practical training. Finally, on the basis of these fi ndings, we recommended, as previously suggested by Ray et al (1994), that junior doctors should not perform ABI measurements alone until they have performed several ABI procedures under supervision with an appropriately experienced instructor [12,19].…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical approach, as adopted by most French Medical Faculties to record the resting ABI, would probably be inappropriate [38]. Regarding ABI, a certain number of measurements must be recorded to build up competence [6,39,40]. Studies conducted by Scissons highlight a better system for classifying Doppler waveform morphologies with the person gaining experience with every waveform analysis [8,10].…”
Section: Teaching Methodsmentioning
confidence: 99%
“…This disease generates a signifi cant morbidity-mortality rate with an estimated cardiovascular mortality rate of 15 to 30 % within fi ve years [4]. The diagnosis of PAD is primarily based on the use of the resting ankle-brachial pressure index (ABI), an ABI < or = 0.90 defi ning PAD [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…4 In this regard, the report of Donnou and colleagues 5 in this issue of Vascular Medicine can be considered as the first attempt to scientifically assess an ABI teaching experience, through a randomized trial with a satisfying number of trainees (n=30). The trial was designed to assess the experiential component of the teaching after didactic learning for all students.…”
mentioning
confidence: 99%